Modelling of Adsorption Kinetic and Equilibrium Isotherms of Hydrogen Sulfide onto Hydrogel Biochar Adsorbent - Bahari Alias, Azil; Ariff Amir Hamzah, Muhamad; Hidayah Meri, Nor; Muhammad Faisal Mat Yasin, Nik; Abdul Rashid, Zulkifli; Azlina Wan Ab Karim Ghani, Wan (International Journal of Engineering and Technology, 2018)
Every process produces byproducts, and it can be dangerous or not. Hydrogen sulfide (H2S) is one of the dangerous byproducts produced. In order to prevent hydrogen sulfide from harming workers or residents, a control system is required. Currently, all industries have a control system such as an adsorption system, to control dangerous component such as H2S. In order to optimize the adsorption system, research is required. Researching using laboratory method is very dangerous due to the harmful nature of H2S. Thus, isotherm and kinetic model is used as an alternative method, as it doesn’t involve H2S usage in laboratory. Each isotherm model and kinetic model equation has different uses for adsorption process. The main objective of this experiment is to find the most suitable equation for adsorption of hydrogen sulfide. The isotherm models used were Langmuir, Freundlich and Elovich, while kinetic models used were Pseudo-First Order and Pseudo-Second Order. Suitability of equation was determined by correlation coefficient (R2). The higher the R2, the more suitable the equation is to process. After the result obtained, comparison was done, comparing R2 of each model. It was found that the most suitable isotherm and kinetic model were Elovich model and Pseudo-Second Order model respectively.  R2 for Elovich model was 0.9686; the highest correlation coefficient among isotherms, while R2 for Pseudo-Second Order model was 0.9284, highest among kinetic models.